Concept of Science and Islamic Intellectual Movements - Hidayatullah; Ismail, Fajri; Zuhdiyah; Sukardi, Ismail; Ramadoni, Muhamad Afdoli (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2025)
Knowledge serves as the fundamental pillar of civilizational advancement, including within the Islamic tradition, which possesses a distinctive and comprehensive epistemological framework. Islamic epistemology perceives knowledge not merely as the product of reason and empirical observation, but also as a spiritual process grounded in divine revelation, particularly the Qur'an. Through a genitivus subjectivus approach, Islam is positioned as the starting point of intellectual inquiry, framing the pursuit of knowledge as both a form of worship and a religious obligation. During its golden age, Islamic civilization successfully cultivated a holistic intellectual tradition that harmoniously integrated religion, philosophy, and science. Muslim scholars not only preserved the legacy of earlier knowledge but also made significant original contributions across diverse fields. However, the dynamism of Islamic intellectual life later declined due to various internal and external factors. In recent times, there has been a renewed effort to revitalize the Islamic scholarly tradition in ways that are ethically grounded and relevant to contemporary challenges. This study aims to explore the concept of Islamic epistemology, the sources and methodologies of knowledge in Islam, and the historical evolution of Islamic intellectual movements from the classical era to the present day. Such an understanding is essential for shaping an ethical, integrative, and contextually relevant development of Islamic knowledge in the global era.